Law under Algorithmic Pressure: A Critical Review of Viral Cases and Digital Public Opinion - Murtadlo, Muhammad Ali; Saputra, Wahyu (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
The phenomenon of virality on social media has introduced new dynamics into the Indonesian judicial system. This article aims to critically examine how public opinion developing on social media, particularly in viral cases, can influence the direction and outcomes of legal decisions. Employing the approach of Critical Legal Studies (CLS) and media sociology perspectives, this paper explores the role of algorithms as invisible actors that generate social pressure on law enforcement authorities. Case studies of several viral legal proceedings in Indonesia indicate the presence of public opinion interventions in judicial processes. This study applies a qualitative-descriptive method with a library research approach. Data were collected from various literature sources and analyses of social media interactions concerning the Ferdy Sambo case. The findings reveal that public opinion on social media plays a crucial role in shaping societal perceptions of justice and fostering transparency in law enforcement. High levels of public participation often demand greater accountability from legal authorities. However, the inability to regulate such participation can lead to legal distortion, posing risks to the objectivity of judicial processes. Therefore, while public opinion may serve as a constructive instrument of social control, the legal system must be upheld independently.